The role of talent development on business performance in Islamic rural banks - Nurfadilah, Dety; Samidi, Sudarmawan; Daryanto, Wiwiek Mardawiyah (Frontiers in Education, 2022)
The objective of this study is to investigate the impact of talent development toward strategic flexibility, digital readiness, and innovativeness and how these also affect the business performance. This study used a quantitative approach using surveys from 391 managers and directors of Islamic rural banks in Indonesia, then the data were analysed using structural equation modelling - partial least square (SEM-PLS). The results show that talent development has positive effects on innovativeness, strategic flexibility, and digital readiness. Moreover, strategic flexibility has positive mediating variables between digital readiness and innovativeness which also lead to business performance. This study provides contribution to the literature by integrating the digital readiness, strategic flexibility and innovativeness toward financial and non-financial performance. It also offers managerial implication that talent development drives those correlations.